Precise identification of immunotherapeutic targets for solid malignancies using clues within the tumor microenvironment—Evidence to turn on the LIGHT. (2nd January 2016) - Maker, Ajay V.
ABSTRACT: Targeted immunotherapy for solid gastrointestinal malignancies is challenging due to a lack of identified tumor antigens. Therefore, a strategy that supports and expands tumor infiltrating lymphocytes in the tumor microenvironment may allow these tumor-reactive T-cells to incite an antitumor response. Gene expression analysis of colon metastases has identified specific immunotherapeutic targets for this malignancy.